THE EFFECTIVENESS OF USING PICTURE SERIES TO TEACH WRITING IN SMPN 1 WARU PAMEKASAN - Yuliarsih Yuliarsih (KABILAH : Journal of Social Community, 2016)
Abstrak: Menulis  sebagai salah satu keterampilan bahasa yang diberikan untuk mendorong  pengajaran bahasa Inggris dari smp sampai universitas khususnya sekolah yang berbahasa Inngris. Sayangnya murid-murid kemampuannya masih rendah. Dan salah satu alasan  adalah metode pendekatan, tehnik yang digunakan oleh guru dan proses pengajaran dan pembelajaran. Lebih-lebih materi yang digunakan kadang-kadang sangat susah untuk dimengerti. Dan proses pembelajaran guru menggunakan banyak media seperti picture series dan movie . Sebagai tambahan dalam pembelajaran ini ditujukan untuk menginvestigasi keefektifan penngunaan picture series untuk mengajar menulis descriptive di smpn 01 waru. Rumusan masalah dan penelitian adalah apakah murid yang diajari picture series mempunyai kemampuan menulis descriptive lebih baik daripada murid yang tidak diajari picture series. Tujuan penelitian dalam penelitian ini adalah untuk menjawab dan menginvestigasi keefektifan picture series terhadap kemampuan menukis descriptive anak.  Design penelitiannya adalah eksperimental design khususnya quasi experimental design karena pembelajaran ini membawa kelas dimana random tidak bisa dilakukan. Subjek dalam penelitian ini terdiri dari 60 murid dari kelas pertama smpn 01 waru pamekasan. Semua subjek dalam pembelajaran mempunyai level yang sama. Hasil dari penelitian menunjukkan bahwa murid setelah diajari menggunakan picture series dalam menulis descriptive mempunyai kemampuan menulis lebih baik daripada murid yang tidak diajari picture series. Ini dibuktikan dari data analisis dan tes hipotesis dengan menggunakan level of signifikan 1% dimana computed t value (4,34) lebih tinggi dari t critical value (2,390). Itu berarti Ha diterima. Kesimpulannya bahwa picture series memberikan pengaruh signifikan terhadap kemampuan menulis anak . Kata Kunci: Kemampuan menulis, Picture seriesAbstract: Writing as one of the language skills is given the most emphasis in the teaching of English from junior to the senior high school and even in university especially for those schools majoring in English. Unfortunately, the students’ writing ability is still low, and one of the reasons is the method, approaches and techniques used by the teacher in teaching and learning process of writing. Moreover,the writing materials used was sometimes very difficult to understand. In the learning process the teacher used many kinds of media such as Picture Series and Movie. In addition, in this study is aimed to investigate the effectiveness of using Picture Series to teach writing in SMPN 1Waru Pamekasan.The research problem of this research: do thestudents taught by Picture Series have better achievement in writing descriptive text than those taught by non Picture Series. The research objective of this research is to answer and investigate the effectiveness Picture Serieson the students writingdescriptive.The researchdesign was experimental design specificallyquasiExperimental designbecause this study is carried out in classroom setting where random assignment to subject could not be conducted. The subject of this research was consisted of 60 students from the first grade of SMPN 1 Waru Pamekasan. All the subjects of this study were at the same class in firstSMPN 1 Waru Pamekasanclass.The result of the research showed that the students after taught by using Picture Series in Writing Descriptive has better achievement in the posttest than the students taught by non-Picture Series.It proved from the data analysis and the hypotheses testing by using level of significant 1% where the computed t-value (4.34) was higher than t-critical value (2.390). The finding means that the Alternative Hypothesis is accepted.It concludes that the using of Picture Series give a significant effect on the students writing achievement. Key words: Writing Achievement, Picture Series